2023
DOI: 10.1097/ccm.0000000000005791
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Magnitude and Timing of Fluid Overload on Outcomes in Critically Ill Children: A Report From the Multicenter International Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology (AWARE) Study

Abstract: OBJECTIVES:With the recognition that fluid overload (FO) has a detrimental impact on critically ill children, the critical care nephrology community has focused on identifying clinically meaningful targets for intervention. The current study aims to evaluate the epidemiology and outcomes associated with FO in an international multicenter cohort of critically ill children. The current study also aims to evaluate the association of FO at predetermined clinically relevant thresholds and time points (FO ≥ 5% and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Finally, common to such large epidemiological studies in children in intensive care is the steady attrition due to early intensive care discharge for large proportions of children. In the study by Selewski et al (1), only 40% of children remained in intensive care by day 3 suggesting most children had low illness severity. Furthermore, only 31% received mechanical ventilation.…”
Section: To the Editormentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, common to such large epidemiological studies in children in intensive care is the steady attrition due to early intensive care discharge for large proportions of children. In the study by Selewski et al (1), only 40% of children remained in intensive care by day 3 suggesting most children had low illness severity. Furthermore, only 31% received mechanical ventilation.…”
Section: To the Editormentioning
confidence: 97%
“…To the I n an international, multicentre study of over 5,000 children and young adults, Selewski et al (1) report the epidemiology and adverse outcomes associated with thresholds of fluid accumulation in terms of magnitude and timing. They found that thresholds of fluid accumulation of 5% and 10% were associated with important adverse outcomes.…”
Section: E169mentioning
confidence: 99%
See 1 more Smart Citation
“…However, uid shifts over the course of disease result in extravascular uid accumulation, consequent hypoxemia, and organ dysfunction(s). (3) Persistence of a positive uid balance (PFB) has been independently associated with poor clinical outcomes among patients with sepsis (4)(5)(6)(7)(8)(9). Complicating matters further, patients may develop sepsis associated acute kidney injury (SA-AKI) and oliguria.…”
Section: Introductionmentioning
confidence: 99%
“…Our study uniquely determines the specific impact of phase of illness by evaluating the timing (end of ICU days 1 and 2), in conjunction with FB threshold (5% and 10%), of when the transition occurs from positive FB to FO (5). This adds the element of timing to describe the transition of positive FB to the pathologic state of FO.…”
mentioning
confidence: 99%